Lindy Chamberlain (Sydney : [Harry M Miller Management Group], 2005)
Includes information about Lindy Chamberlain-Creighton and her book; everything that followed, available to the merely curious, and researcher alike.
Title from title screen (viewed on 26 June 2006).
Text and graphics.
Mode of access: Internet via World Wide Web. Available at: http://www.lindychamberlain.com/content/home
System requirements: Adobe Acrobat reader required to view/print pdf files.
Selected for archiving
Keywords: Chamberlain-Creighton, Lindy, -- 1948-; Chamberlain-Creighton, Lindy, -- 1948- -- Trials, litigation, etc; Absence and presumption of death -- Northern Territory -- Ayers Rock; Trials (Infanticide) -- Northern Territory -- Darwin